Caracterização hidrogeoquímica e ecotoxicológica do sedimento de fundo, da água e do sedimento em suspensão transportado pela microbacia do Ribeirão Guamium, rio Piracicaba, SP, em função da sazonalidade - Pereira, Flávia Fontes (2011)
At the Guamium River microbasin, a branch of the Piracicaba Basin, SP, superficial water, bottom and suspended sediments were selected as natural compartments to assess for the ecosystem degradation due to the intensive land usage. Sampling campaign were carried out during one year in a seasonal approach. Discharge and precipitation data were obtained monthly. At the field, pH, temperature, dissolved oxygen (DO), electrical conductivity (EC) and total dissolved solids (TDS) were measured and in water samples collected at ten sampling points, Ca+2, Mg+2, K+, NH4 +, Na+, SO4 -2, PO4 -3, NO3 -, Br-, NO2 -, Cl- and HCO3 - were determinate at the laboratory by ion chromatography and Gran titration. The dissolved discharge for Ca, Mg, K and Na were calculated. The suspended particulate matter, which were only measured at the low third part of the basin, were analysed for soil exchangeable cations (Ca, Mg, K, Na), N, P and total As. In addition, δC13 e δN15, were also determinated in order to evaluate the land use in the basin. The solid discharge and transport of Ca, Mg, K, Na and P on it were calculated. Bottom sediments, sampled at 10 sampling points, were evaluated for C, N, C/N rate, bioavailable and total As, being it δC13 e δN15 established. Bottom sediment toxicity were evaluated by both, algae bioassay, Pseudokirchneriella subcapitata and volatile acid sulphides (VAS). Although TDS and EC were high in some sampling points, most of ion concentrations were in the allowed ranges required for CONAMA 357/05. The transport of the dissolved soil exchangeable cations were around Kg h-1. The solid discharge, considering a precipitation of 447,40 mm, were 90,34 Kg h-1; 35,45 Kg h-1; 13,08 Kg h-1, 6,71 Kg h-1 and 25,47 Kg h-1 , for Ca, Mg, K, Na and P, respectively. The observed variation for %C13 varied from 6% to 82% in the bottom sediments and 9% to 48% in the suspended one, emphasizing the occurrence of C4 plants in the basin. High toxicity were observed at P5 in the dry season (August, 2010) and at P1 in the rainy one (March, 2011), which leads to a low growing curves and lower cells density when compared to the control. These data were not in accordance to the AVS/ΣSEM, which indicates the potential toxicity in the medium. Total As concentrations in the bottom and in the suspended sediments were high and can be due the use of herbicides in agriculture while no correspondence for bioavailable As were achieved for the same substrates.